A Security-Performance-Balanced User Authentication Scheme for Wireless Sensor Networks. (5th March 2012) - Yoo, Sang Guun; Park, Keun Young; Kim, Juho
Abstract : The uses of wireless sensor networks have increased to be applicable in many different areas, such as military applications, ecology, and health applications. These applications often include the management of confidential information, making the issue of security one of the most important aspects to consider. In this aspect, a user authentication mechanism that allows only legitimate users to access the network data becomes critical for maintaining the confidentiality and integrity of the network information. In this paper, we describe and cryptoanalyze previous works in user authentication to illustrate their vulnerabilities and security flaws. We then propose a robust user authentication scheme that solves the identified limitations. Additionally, we describe how the proposed protocol is more suitable for a secure sensor network implementation by analysis in terms of security and performance.